2011
DOI: 10.1007/s10162-011-0288-x
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1-Mediated Accumulation of Aminoglycosides in Mouse Cochlear Outer Hair Cells

Abstract: Aminoglycoside ototoxicity involves the accumulation of antibiotic molecules in the inner ear hair cells and the subsequent degeneration of these cells. The exact route of entry of aminoglycosides into the hair cells in vivo is still unknown. Similar to other small organic cations, aminoglycosides could be brought into the cell by endocytosis or permeate through large non-selective cation channels, such as mechanotransduction channels or ATP-gated P2X channels. Here, we show that the aminoglycoside antibiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 54 publications
2
68
0
Order By: Relevance
“…A number of alternative entry mechanisms have been proposed in addition to the MET channel or through endocytosis. It has been suggested that AGs enter through other channels including transient receptor potential channels (75)(76)(77). The sodium glucose transporter SLC5A2 may also play a role in AG transport in the kidney (78).…”
Section: Discussionmentioning
confidence: 99%
“…A number of alternative entry mechanisms have been proposed in addition to the MET channel or through endocytosis. It has been suggested that AGs enter through other channels including transient receptor potential channels (75)(76)(77). The sodium glucose transporter SLC5A2 may also play a role in AG transport in the kidney (78).…”
Section: Discussionmentioning
confidence: 99%
“…Styryl dyes enter hair cells via the mechanotransduction channel, endocytotic vesicles, and P2X channels (Balak et al 1990;Nishikawa and Sasaki 1996;Griesinger et al 2002;Meyers et al 2003;Griesinger et al 2004;Marcotti et al 2005;Kaneko et al 2006;Crumling et al 2009). Ototoxic aminoglycosides also enter hair cells through multiple routes including the mechanotransduction channel, endocytosis, chloride/bicarbonate exchangers, and TRPA1 channels (Alharazneh et al 2011;Stepanyan et al 2011;Hailey et al 2012). This is the first reported evidence of living hair cells taking up phalloidin.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the pattern of a differential gradient for basal to apical uptake did not persist beyond 3 h. More recently, attention has focused on ion channels in hair cells (Marcotti et al 2005 ). Transient Receptor Potential channels (trpv1, trpv4, trpa1, and trpp1) are nonselective cation channels that appear to permit aminoglycoside entry (Stepanyan et al 2011 ). Mechanoelectrical transduction (MET) channels are necessary for aminoglycoside ototoxicity (Alharazneh et al 2011 ).…”
Section: Cellular Uptake and Pharmacokineticsmentioning
confidence: 99%